2016
DOI: 10.1186/s41100-016-0069-4
|View full text |Cite
|
Sign up to set email alerts
|

Triglyceride to high-density lipoprotein cholesterol ratio predicts cardiovascular events in maintenance hemodialysis patients

Abstract: Background: The triglyceride to high-density lipoprotein cholesterol (TG/HDL-C) ratio has been shown to be a predictor of cardiovascular (CV) outcomes in the general population. The aim of this study was to determine whether the TG/HDL-C ratio is a predictor of CV events and all-cause mortality in maintenance hemodialysis (MHD) patients. Methods: We performed a retrospective, observational cohort study in which we enrolled 193 MHD patients from a single center in Japan who had been followed up for a median of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 38 publications
2
13
2
Order By: Relevance
“…Similarly, a level of TG was significantly higher in only patients with MA (20) and elsewhere shows no significant differences (21). This study strongly highlights higher risk of CVD among migraineurs, as we identified phenotypic and genetic overlap between migraine and a lower level of HDL-C, known as good cholesterol, and increased levels of CVD risk chemistry tests (22), including TC/ HDL-C (cholesterol ratio), TG/HDL-C ratio, LDL-C and TG. Consistent with our finding, a recent metabolome study found decreased levels of apolipoprotein A1 and free cholesterol to total lipid ratio in small HDL-C in migraine patients (23), reflecting a reduced level of HDL-C metabolism.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Similarly, a level of TG was significantly higher in only patients with MA (20) and elsewhere shows no significant differences (21). This study strongly highlights higher risk of CVD among migraineurs, as we identified phenotypic and genetic overlap between migraine and a lower level of HDL-C, known as good cholesterol, and increased levels of CVD risk chemistry tests (22), including TC/ HDL-C (cholesterol ratio), TG/HDL-C ratio, LDL-C and TG. Consistent with our finding, a recent metabolome study found decreased levels of apolipoprotein A1 and free cholesterol to total lipid ratio in small HDL-C in migraine patients (23), reflecting a reduced level of HDL-C metabolism.…”
Section: Discussionsupporting
confidence: 61%
“…Padhraig Gormley 1-4,* , Verneri Anttila 2,3,5,* , Bendik S Winsvold [6][7][8] , Priit Palta 9 , Tonu Esko 2,10,11 , Tune H Pers 2,[11][12][13] , Kai-How Farh 2,5,14 , Ester Cuenca-Leon [1][2][3]15 , Mikko Muona 9,[16][17][18] , Nicholas A Furlotte 19 , Tobias Kurth 20,21 , Andres Ingason 22 , George McMahon 23 , Lannie Ligthart 24 , Gisela M Terwindt 25 , Mikko Kallela 26 , Tobias M Freilinger 27,28 , Caroline Ran 29 , Scott G Gordon 30 , Anine H Stam 25 , Stacy Steinberg 22 , Guntram Borck 31 , Markku Koiranen 32 , Lydia Quaye 33 , Hieab H H Adams 34,35 , Terho Lehtim€ aki 36 , Antti-Pekka Sarin 9 , Juho Wedenoja 37 , David A Hinds 19 , Julie E Buring 21,38…”
Section: Ihgc Members Contributing To the Gormley Et Al (2016) Migraine Gwasmentioning
confidence: 99%
“…We have previously reported an interaction between the TG/HDL-C ratio and DM in the prediction of CV events [22]. This finding is also consistent with the interaction exists between them in predicting events in the general population, and patients with a high TG/HDL-C ratio have been reported to be predisposed to diabetes mellitus [25].…”
Section: Discussionsupporting
confidence: 76%
“…Kilpatrick et al [21] demonstrated that HDL-C and TG did not to predict CV or all-cause mortality in a large HD cohort who were followed up for 3 years. We previously used the TG/HDL-C ratio to predict all-cause mortality and CV events, and the results clearly demonstrated the predictive power of the TG/HDL-C ratio in MHD patients [22]. Chen et al [23] have recently demonstrated the predictive ability of the TG/HDL-C ratio for CV outcomes and survival in patients undergoing prevalent dialysis.…”
Section: Discussionmentioning
confidence: 99%
“…No study to date has shown that lowering cholesterol extends overall survival. A number of observational cohort studies in a variety of settings found that all-cause mortality has a "U", "J", or "L" shaped relationship to serum cholesterol (Bowe et al, 2016;Hasegawa et al, 2016). Therefore, this study aimed to determine if low serum cholesterol (< 160 mg/dl) is a risk factor for non-CVD mortality.…”
Section: The Association Between Low Serum Cholesterol and Non-cardiomentioning
confidence: 99%